THE USE OF ICT IN “DISCRETE MATHEMATICS” METHODICAL SYSTEM OF EDUCATION FOR THE FORMATION OF INFORMATION COMPETENCE (Journal of Information Technologies in Education (ITE), 2012)
The article deals with the implementation of information and communication technologies in educational system of "Discrete Mathematics" as a way to formation of students’ information competence.
Keywords: discrete mathematics; information competence; methodical system of education